Why employees go green? Unpacking roles of leadership and green motivation on pro-environmental behaviours in China's new energy vehicle sector - Zhang, Yidi; Xia, Bo; Dong, Haihui; Pu, Ruihui (Allan); Anser, Muhammad Khalid (Elsevier B.V., 2026)
Drawing on self-determination theory and social cognitive theory, this mixed-methods study examines how green transformational leadership (GTL) influences dimensions of employee pro-environmental behavior (PEB)—namely, eco-initiatives, eco-helping, and eco-civic engagement—in China’s new energy vehicle (NEV) sector. We propose that green motivation, comprising intrinsic green motivation (e.g., personal values and interests) and extrinsic green motivation (e.g., recognition and incentives), mediates the relationship between GTL and PEB. Quantitative data were analyzed using covariance-based structural equation modeling. Survey data from 504 employees in the Chinese NEV sector indicate that GTL positively relates to all three PEB dimensions, with green motivation serving as a significant mediator. Subsequently, in-depth interviews with 10 practitioners in the new energy sector provided complementary insights into mechanisms not fully captured in the quantitative phase. These findings help address underexplored mechanisms in the existing literature. Specifically, intrinsic motivation is significantly influenced by extrinsic motivation, and extrinsic motivation is closely related to factors such as organizational welfare policies, incentive mechanisms, specific measures, and return rates. Interview results show that articulating a compelling green vision and modeling environmental commitment enhance intrinsic motivation, whereas implementing structured incentive systems and public recognition activate extrinsic motivation. These motivational pathways collectively empower employees to undertake proactive, collaborative, and civic-oriented environmental actions. Although previous studies have demonstrated the importance of macro-economic performance and micro-foundations of sustainability in NEV firms, our study further examines the integration of leadership, motivation, and behavior, offering a nuanced framework for understanding how leaders’ motivational influence can differentially stimulate varied forms of green behavior in environmentally intensive industries.